Should Abdominal Aortic Aneurysms in Women be Repaired at a Lower Diameter Threshold?. (October 2018) - Deery, Sarah E.; Schermerhorn, Marc L.
Abdominal aortic aneurysm (AAA) primarily affects male patients; however, female patients with AAA have a faster rate of aneurysm growth, have higher risk of rupture even at smaller diameters, and have worse outcomes following repair of ruptured and intact aneurysms. Furthermore, early natural history studies and randomized controlled trials evaluating surveillance versus repair in small aneurysms were conducted primarily in male patients. Therefore, there are limited data regarding the ideal threshold for elective repair of AAA in women, either by aortic diameter or by alternative measures. We review the existing literature regarding AAA in women and consider the most appropriate threshold for repair.